A new self-calibration method applied to TOMS and SBUV backscattered ultraviolet data to determine long-term global ozone change - Herman, J. R.; Hudson, R.; Mcpeters, R.; Stolarski, R.; Ahmad, Z. (1991)
The currently archived (1989) total ozone mapping spectrometer (TOMS) and solar backscattered ultraviolet (SBUV) total ozone data (version 5) show a global average decrease of about 9.0 percent from November 1978 to November 1988. This large decrease disagrees with an approximate 3.5-percent decrease estimated from the ground-based Dobson network. The primary source of disagreement was found to arise from an overestimate of reflectivity change and its incorrect wavelengths dependence for the diffuse plate used when measuring solar irradiance. Both of these factors have led to an overestimate of the rate of atmospheric ozone depletion by SBUV and TOMS. For total ozone measured by TOMS, a means has been found to use the measured radiance-irradiance ratio from several wavelengths pairs to construct an internally self-consistent calibration. The method uses the wavelength dependence of the sensitivity to calibration errors and the requirement that albedo ratios for each wavelength pair yield the same total ozone amounts. Smaller errors in determining spacecraft attitude, synchronization problems with the photon counting electronics, and sea-glint contamination of boundary reflectivity data have been corrected or minimized. New climatological low-ozone profiles have been incorporated into the TOMS algorithm that are appropriate for Antarctic ozone hole conditions and other low ozone cases. The combined corrections have led to a new determination of the global average total ozone trend (version 6) as a 2.9 + or - 1.3 percent decrease over 11 years (October 1978 to November 1989).